Enriching Hippocampal Memory Function in Older Adults Through Real-World Exploration - Kolarik, Branden S.; Stark, Shauna M.; Stark, Craig E. L. (Frontiers in Aging Neuroscience, 2020)
Age-related structural and functional changes in the hippocampus can have a severe impact on hippocampal-dependent memory performance. Here, we tested the hypothesis that a real-world spatial exploration and learning intervention would improve hippocampal-dependent memory performance in healthy older adults. We developed a scavenger hunt task that participants performed over the course of a four-week behavioral intervention period. Following this intervention, participants’ lure discrimination index (LDI) on the Mnemonic Similarity Task was significantly higher than it was at baseline and greater than that of a No-Contact Control Group, while traditional recognition scores remained relatively unchanged. These results point to the viability of a spatial exploration intervention for improving hippocampal-dependent memory in older adults.